Study and Evaluation of public kindergartens (Future Roses kindergarten in the Qudsia suburb) (Damascus University Journal of agriculture sciences, 2021)
This work was conducted in the Future Roses Kindergarten at Qudsia Suburb in 2017. The field study was done for the kindergarten to identify it, (The outside area) which is a garden of the kindergarten, in terms of location, area, and inventory of natural and structural elements after lifting of the current status of the setback, The kindergarten' setback was evaluated from the parents of children’ point of views concerning of ensuring the requirements of children through a questionnaire which was accomplished by 200 parents. The results showed after evaluation of the kindergarten' setback were satisfied partially because of the lack of any service facilities or elements of entertainment, and the absence of cultivated areas, And the lack of inadequate play equipment, in addition to non-diversity and lack of maintenance periodically. The questionnaire was also used to identify the wishes of the children's parents if the kindergarten' setback was transferred to a garden. Accordingly, the garden of kindergarten was designed according to applying scientific methodology that should be followed when studying kindergartens
Keywords: design and landscaping; green spaces; kindergarten gardens; questionnaire